2012
DOI: 10.1017/s0025315411002165
|View full text |Cite
|
Sign up to set email alerts
|

Brooding and sperm storage by the deep-sea squid Bathyteuthis berryi (Cephalopoda: Decapodiformes)

Abstract: Squids of the family Bathyteuthidae have generally been infrequently encountered in their deep-sea habitat. Remotely operated vehicles were used to observe seven individuals in situ in the Monterey Submarine Canyon, CA, USA. One of these was a female Bathyteuthis berryi holding a sheet with approximately 360 embedded embryos. Examination of this female after collection revealed the presence of a seminal receptacle on the buccal membrane. We present some potential costs and benefits of post-spawning egg care, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
24
1
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(29 citation statements)
references
References 37 publications
2
24
1
2
Order By: Relevance
“…In Muusoctopus longibrachus ak am bei, the total number of POF (139− 251) was also similar to the fecundity of mature females (75−234 eggs; Laptik - The number of POF might be a good tool to estimate actual fecundity in brooding deep-sea and polar octopodids when egg mass is not available, as was shown for some deep-sea and Antarctic squids (Nesis et al 1998, Laptik hovsky et al 2007, Bush et al 2012. In these studies, the unimodal distribution of their size indicated that eggs were released more or less as a single batch or a few mini-batches separated by very short periods of time.…”
Section: Discussionmentioning
confidence: 71%
See 3 more Smart Citations
“…In Muusoctopus longibrachus ak am bei, the total number of POF (139− 251) was also similar to the fecundity of mature females (75−234 eggs; Laptik - The number of POF might be a good tool to estimate actual fecundity in brooding deep-sea and polar octopodids when egg mass is not available, as was shown for some deep-sea and Antarctic squids (Nesis et al 1998, Laptik hovsky et al 2007, Bush et al 2012. In these studies, the unimodal distribution of their size indicated that eggs were released more or less as a single batch or a few mini-batches separated by very short periods of time.…”
Section: Discussionmentioning
confidence: 71%
“…However, terminal spawning seems to be a strange evolutionary choice for these habitats, particularly because cirrate octopods that live at similar depth ranges and produce eggs of similar size exhibit continuous spawning with eggs laid individually (Villanueva 1992, Laptikhovsky 1999a. A phenomenon similar to single-batch terminal spawning also exists in the deep-sea squid families Onychoteuthidae, Cranchidae, Gonatidae and Bathyteuthidae (Seibel et al 2000, Laptikhovsky & Arkhipkin 2003, Laptikhovsky et al 2007, Bush et al 2012, of which at least Gonatidae and Bathyteuthidae are also brooders. In contrast to octopods, females of these squid families carry the egg mass in their arms, so they are not able to feed even occasionally during the incubation period.…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…The location of the specialized area for spermatangia reception of A. lesueurii resembles the paired receptacles beneath the collar of some Enoploteuthidae (Burgess 1998), although some enoploteuthids have wrinkled outer collar tissue, which was not found in A. lesueurii. In general the "seminal receptacles" (here called specialized areas for spermatangia reception) of the enoploteuthid group of families (Ancistrocheiridae, Enoploteuthidae, Lycoteuthidae and Pyroteuthidae) differ structurally from the seminal receptacles of loliginids, ommastrephids and bathyteuthids (Nesis 1995;Bush et al 2012). In these latter families, sperm from spermatangia that are attached in the buccal area are removed or migrate into a closed storage organ present on the buccal membrane.…”
Section: Discussionmentioning
confidence: 99%